Association of the ADORA2A receptor and CD73 polymorphisms with epilepsy - Shi, Nan-Rui; Wang, Qi; Liu, Jie; Zhang, Ji-Zhou; Deng, Bin-Lu; Hu, Xiu-Min; Yang, Jie; Wang, Xin; Chen, Xiang; Zuo, Yan-Qin; Liu, Ting-Ting; Zheng, Jia-Ling; et al. (Frontiers in Pharmacology, 2023)
Single-nucleotide polymorphisms are in connection with the risk of epilepsy on occurrence, progress, and the individual response to drugs. Progress in genomic technology is exposing the complex genetic architecture of epilepsy. Compelling evidence has demonstrated that purines and adenosine are key mediators in the epileptic process. Our previous study found the interconnection of P2Y12 receptors single-nucleotide polymorphisms and epilepsy. However, little is known about the interaction between the purine nucleoside A2A receptor and rate-limiting enzyme ecto-5’-nucleotidase/CD73 and epilepsy from the genetic polymorphism aspect. The aim of the study is to evaluate the impact of A2AR and CD73 polymorphisms on epilepsy cases. The study group encompassed 181 patients with epilepsy and 55 healthy volunteers. A significant correlation was confirmed between CD73 rs4431401 and epilepsy (p<0.001) with TT genotype frequency higher and C allele lower among epilepsy patients in comparison with healthy, indicating that the presence of the TT genotype related to an increased risk of epilepsy (OR=2.742, p=0.006), while carriers of the C allele demonstrated a decreased risk of epilepsy (OR=0.304, p<0.001). According to analysis based on gender, the allele and genotype of rs4431401 in CD73 were associated with both male and female cases (p<0.0001, p=0.026, respectively). Of note, we found that A2AR genetic variants rs2267076 T>C (p=0.019), rs2298383 C>T (p=0.039), rs4822492 T>G (p=0.029), and rs4822489 T>G (p=0.029) were only associated with epilepsy in female subjects instead of male. It is evident that the TT genotype and T allele of rs4431401 in CD73 were genetic risk factors for epilepsy, whereas rs2267076, rs2298383, rs4822492, and rs4822489 polymorphisms of the A2AR were mainly associated with female subjects.